2021
DOI: 10.1186/s40635-021-00389-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of targeting Tie2 on hemorrhagic shock-induced renal perfusion disturbances in rats

Abstract: Background Hemorrhagic shock is associated with acute kidney injury and increased mortality. Targeting the endothelial angiopoietin/Tie2 system, which regulates endothelial permeability, previously reduced hemorrhagic shock-induced vascular leakage. We hypothesized that as a consequence of vascular leakage, renal perfusion and function is impaired and that activating Tie2 restores renal perfusion and function. Methods Rats underwent 1 h of hemorrha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…THS induces systemic inflammation, leading to a permeable endothelium, tissue edema and organ injury [9,10]. We and others have previously shown reduced endothelial Tie2 expression, endothelial hyperpermeability and organ injury in animals following HS [10,12,21] and sepsis [21,30] and in postmortem renal tissue of septic patients [36]. To study the effect of reduced Tie2 expression without additional effects such as systemic inflammation, we have included heterozygous Tie2 knockout mice.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…THS induces systemic inflammation, leading to a permeable endothelium, tissue edema and organ injury [9,10]. We and others have previously shown reduced endothelial Tie2 expression, endothelial hyperpermeability and organ injury in animals following HS [10,12,21] and sepsis [21,30] and in postmortem renal tissue of septic patients [36]. To study the effect of reduced Tie2 expression without additional effects such as systemic inflammation, we have included heterozygous Tie2 knockout mice.…”
Section: Plos Onementioning
confidence: 99%
“…THS causes a systemic inflammatory response that activates the endothelium [9]. This results in increased endothelial permeability, leakage of fluids into the interstitium and tissue edema [10]. We have previously shown that plasma from male THS patients induces endothelial hyperpermeability in vitro [11] and that THS in male rats induces vascular leakage in both lung and kidney [12].…”
Section: Introductionmentioning
confidence: 99%